2013
DOI: 10.3109/02813432.2013.788270
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in patients with acute rhinosinusitis is not in agreement with European recommendations

Abstract: ObjectiveTo assess the potential overprescribing in patients with acute rhinosinusitis across six countries with different antibiotic prescribing rates and different prevalence of antibiotic resistance.Design, setting and subjectsA cross-sectional study including GPs from two Nordic countries, two Baltic countries and two Hispano-American countries registered patients with respiratory tract infections (RTIs) during three weeks in January 2008 as part of the EU-funded project “Health Alliance for Prudent Prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
1
24
1
2
Order By: Relevance
“…A recent study performed in six countries also showed high rates of antibiotic prescribing in patients with acute sinusitis, ranging from 56% to 87% [6]. About 80% of sinusitis have a viral aetiology, and only a very small percentage is complicated by bacterial infection [15].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study performed in six countries also showed high rates of antibiotic prescribing in patients with acute sinusitis, ranging from 56% to 87% [6]. About 80% of sinusitis have a viral aetiology, and only a very small percentage is complicated by bacterial infection [15].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Despite the fact that the benefit of antimicrobial treatment is rather low [3,4], a substantial number of patients with RTI are treated with antibiotics [5,6]. Diagnostic uncertainty characterizes the management of RTIs and doubt about the diagnosis and the aetiology may lead to antibiotic over-prescribing.…”
mentioning
confidence: 99%
“…EPOS has inspired researchers to use standard definitions of disease, study the epidemiology and management of ARS and CRS, reduce unnecessary (mainly antibiotic) treatment and form new collaborations to answer unmet research questions (9,(21)(22)(23)(24)(25)(26) . EPOS2020 will build on this success.…”
Section: Introductionmentioning
confidence: 99%
“…Viral URTI or allergic rhinitis may lead to secondary bacterial infection of the sinuses. Viral URTI or allergic rhinitis may lead to secondary bacterial infection of the sinuses in about 0.5–2% of cases (6–13% in children) . In bacterial sinusits, Streptococcus pneumoniae , Haemophilus influenzae , and/or Moraxella catarrhalis are common causative organisms .…”
Section: Introductionmentioning
confidence: 99%
“…Viral URTI tends to be self‐limiting, and the treatment is symptomatic (analgesics, antipyretics and/or decongestants) . There is widespread over‐prescription of antibiotics in ARS, which are usually ineffective since most cases represent viral URTI. One evidence‐based protocol advocated that clinicians assume the aetiology of rhinosinusitis is viral if symptoms have been present for less than 10 days and are not worsening.…”
Section: Introductionmentioning
confidence: 99%